High‐Color‐Rendering and High‐Efficiency White Organic Light‐Emitting Devices Based on Double‐Doped Organic Single Crystals - Ding, Ran; Dong, Feng‐Xi; An, Ming‐Hui; Wang, Xue‐Peng; Wang, Mo‐Ran; Li, Xian‐Bin; Feng, Jing; Sun, Hong‐Bo (Advanced functional materials, 2019)
Organic single crystals with much higher carrier mobility and stability compared to the amorphous organic materials have shown great potential in electronic and optoelectronic devices. However, their applications in white organic light‐emitting devices (WOLEDs), especially the three‐color‐strategy WOLEDs, have been hindered by the difficulties in fabricating complicated device structures. Here, double‐doped white‐emission organic single crystals are used as the active layers for the first time in the three‐color‐strategy WOLEDs by co‐doping the red and green dopants into blue host crystals. Precise control of the dopant concentration in the double‐doped crystals results in moderately partial energy transfer from the blue donor to the green and red dopants, and thereafter, simultaneous RGB emissions with balanced emission intensity. The highest color‐rendering index (CRI) and efficiency, to the best of the authors' knowledge, are obtained for the crystal‐based WOLEDs. The CRI of the WOLEDs varies between 80 and 89 with the increase of the driving current, and the luminance and current efficiency reach up to 793 cd m−2 and 0.89 cd A−1, respectively. The demonstration of the present three‐color organic single‐crystal‐based WOLED promotes the development of the single crystals in optoelectronics. High‐color‐rendering and high‐efficiency three‐color‐strategy white organic light‐emitting devices (WOLEDs) are realized using double‐doped white‐emission organic single crystals, which are grown by co‐doping red and green dopants into the blue host. The crystal‐based WOLEDs exhibit the maximum luminance, current efficiency, and external quantum efficiency of 793 cd m−2, 0.89 cd A−1, and 0.48%, respectively, which promote the development of the organic single crystals in optoelectronics.